2023
DOI: 10.2147/idr.s394600
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Antibacterial Potential of Greenly Synthesized Silver Nanoparticles with Fosfomycin Against Some Nosocomial Bacterial Pathogens

Abstract: Introduction A considerable number of morbidities and fatalities occur worldwide as a result of the multidrug resistant microorganisms that cause a high prevalence of nosocomial bacterial infections. Hence, the current investigation was conducted to evaluate the antibacterial potency of green fabricated silver nanoparticles (AgNPs) against four different nosocomial pathogens. Methods The flower extract of Hibiscus sabdariffa mediated green fab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…It is noteworthy that Chloramphenicol (20 μg/mL) and 0.1% DMSO served as the positive and negative controls, respectively. MBC determinations were confirmed by spreading the culture from wells that showed no growth onto nutrient agar plates, following the methodology described by [ 90 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is noteworthy that Chloramphenicol (20 μg/mL) and 0.1% DMSO served as the positive and negative controls, respectively. MBC determinations were confirmed by spreading the culture from wells that showed no growth onto nutrient agar plates, following the methodology described by [ 90 ].…”
Section: Methodsmentioning
confidence: 99%
“…The following bacterial pathogens, comprising Salmonella typhimurium (ATCC 14023), Klebsiella pneumoniae (ATCC 700603), Enterobacter cloacae (ATCC 13047), methicillin-resistant Staphylococcus aureus (ATCC 43300), Escherichia coli (ATCC 25922), and Acinetobacter baumannii (ATCC 43498), were used to determine their sensitivity to the bioprepared ZnO-NPs. Disc diffusion assay was employed to detect the antimicrobial efficacy of the bioinspired ZnO-NPs against the concerned pathogens [ 40 ]. Firstly, the microbial suspension was prepared from fresh bacterial colonies using 0.85% sterilized saline solution then the turbidity was accustomed using 0.5 McFarland standard to acquire viable cell count of 1.0 × 10 8 CFU/mL.…”
Section: Methodsmentioning
confidence: 99%
“…For biomedical applications in particular, it is essential to characterize them thoroughly to determine whether they are suitable for the intended use. This is accomplished by utilizing several techniques and equipment that can provide the required information ( Aljeldah et al, 2023 ).…”
Section: Characterization Of Biogenic Nanoparticlesmentioning
confidence: 99%
“…Monodisperse samples have PDI values below 0.05, while samples with a wide range of particle sizes are more likely to have PDI values above 0.7. The high negative charge of the biogenic NPs indicated that the surface of these nanoparticles was negatively charged ( Aljeldah et al, 2023 ). Using Brookhaven Zeta Plus and dynamic light scattering (DLS) measurements, the hydrodynamic size of the phytofabricated NPs and PDI were assessed using nanoparticle-tracking analysis.…”
Section: Characterization Of Biogenic Nanoparticlesmentioning
confidence: 99%